Workload Indicators of Staffing Need (WISN) for the Required Estimation of Nursing Staff in a Hemodialysis Unit - Feli Clarisa Winvi; Sri Lestari Ramadhani Nasution; Chrismis Novalinda Ginting (Folia Medica Indonesiana, 2023)
Highlights: